(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
At the end of the 20th and the turn of the 21st centuries, humanity faced a global public health problem: obesity [139]. According to forecasts from the World Obesity Federation (WOF), by the middle of this century, more than half of the planet’s population could be overweight or obese [134].